Orthogonal experimental design of polydimethylsiloxane curing for the design of low-frequency vibrational energy harvester. (December 2014) - Xie, Mengying; Aw, Kean; Edwards, Bryn; Gao, Wei; Hu, Patrick
Harvesting vibrational kinetic energy from low-frequency vibrations such as human motion is a promising method to power portable electronic devices. Efficient vibrational energy harvesters can be achieved using structures with a resonant frequency matched to that of the applied vibration; however, the high stiffness of traditional materials such as silicon makes it challenging to create a compact structure with a low resonant frequency. Therefore, polydimethylsiloxane is an attractive candidate. The working frequency can be determined by the material's Young's modulus. The processing parameters, such as curing time, curing temperature, and mixing ratio of base and curing agent, which affect the elastic properties of polydimethylsiloxane, have previously been investigated individually but do not take into account the cross effect of these parameters. Here, for the first time using orthogonal experiment design, these parameters were considered together and two comprehensive equations have been established to model the effect of the curing parameters on the elastic properties of polydimethylsiloxane. The model was verified with additional experiments, and an energy harvester with a predicted natural frequency of ~22 Hz has been fabricated and corroborate with the experimental results.